2023
DOI: 10.1002/edn3.391
|View full text |Cite
|
Sign up to set email alerts
|

Inferring functional diversity from environmental DNA metabarcoding

Abstract: Environmental DNA (eDNA) metabarcoding is a reliable method to assess taxonomic diversity, but the incompleteness of genetic reference databases prevents the assignation of many sequences to a given species. Functional diversity (FD) is a key biodiversity facet to monitor, but it requires the identification of all species within communities to account for their trait values. So, the ability of eDNA‐based inventories to estimate the “true” level of FD is unknown. Here, using fish surveys in two representative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Therefore, seaports and reserves depending on the present communities would have different ecological functions. Characterizing seaports and reserves functions based on identified taxonomic groups based on traits databases would give additional knowledge by indirectly assess ecological functioning of the habitats sampled (Aglieri et al., 2021; Condachou et al., 2023; Marques et al., 2021). This approach would require wide taxonomic coverage and resolution, and would allow to point out which functions are altered in urbanized habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, seaports and reserves depending on the present communities would have different ecological functions. Characterizing seaports and reserves functions based on identified taxonomic groups based on traits databases would give additional knowledge by indirectly assess ecological functioning of the habitats sampled (Aglieri et al., 2021; Condachou et al., 2023; Marques et al., 2021). This approach would require wide taxonomic coverage and resolution, and would allow to point out which functions are altered in urbanized habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Digital-PCR, the latest generation of PCR technology, emerges as a promising candidate among available techniques. dPCR undergoes continuous development in human biology and is increasingly utilized in environmental biology (Condachou et al 2024), offering reliable and absolute quantification, resilient to PCR-reaction inhibitors (Kuypers and Jerome 2017).…”
Section: B Bruxellensis Physiology Presents Challenges For Cultivatio...mentioning
confidence: 99%
“…An interesting simulation on the variability of estimates of functional diversity for fish communities based on eDNA metabarcoding was carried out by Condachou et al (2023). By employing eDNA analysis to infer species composition, they demonstrate that it may be possible to estimate the functional characteristics of a community in conjunction with another database containing functional attributes of the inhabiting organisms.…”
Section: Applying Edna or Erna To Te S T Ecolog I C Al Or B I Olog I ...mentioning
confidence: 99%
“…The assessment of functional diversity, however, may be influenced by uncertainty in the taxonomic assignment of species due to variations in taxonomic granularity. Condachou et al (2023) manipulate the uncertainty in the taxonomic assignment for fish species and found that misidentification of species within the same genus or family did not cause variability in functional diversity higher than 30% in comparison with a case with perfect taxonomic identification at the species level. This is a case study focusing on two sample rivers, but it raises warning flags for the general functional diversity estimation based on metabarcoding data.…”
Section: Applying Edna or Erna To Test Ecological Or Biological Quest...mentioning
confidence: 99%